Factors Influencing the Efficiency of Malaysian Local Governments - Mohd Said, Julia; Mohd Amin, Husniyati; Ismail, Suhaiza (Asian Journal of Accounting Perspectives, 2020)
Research aim: This paper investigates the factors influencing the efficiency of Malaysian local governments. Three measures of efficiency are considered, namely (i) technical efficiency (TE), (ii) pure technical efficiency (PTE) and (iii) scale efficiency (SE). Design/ Methodology/ Approach: This study uses secondary data from annual financial statements of local governments in Malaysia. Financial statements from 2008 to 2015 from 35 local governments were obtained. Panel regression based on the ordinary least square was used to examine the determinants of efficiency of the Malaysian local governments. Research findings: The results reveal that the population size and value of assets have positive and significant influence on the PTE, economic independence has positive and significant influence on the TE and SE, while the dependence on tax revenues is found negatively and significantly associated with all the three measures of efficiency (i.e. TE, PTE and SE). Originality/value: The paper provides empirical evidence on the determinants of efficiency of local governments in Malaysia. More importantly, the investigation on the factors was carried out for three measures of efficiency that are TE, PTE and SE. Practitioner/ Policy implication: The findings offer useful information to the relevant local governments in improving their efficiency. Research limitation: The present study has focused only on examining the efficiency of local government and has not been able to assess the effectiveness of these services. Keywords: Determinants for Efficiency, Local Government, Malaysia Type of article: Research paper JEL Classification: H72